Shoot-Root Communication Plays a Key Role in Physiological Alterations of Rice (Oryza sativa) Under Iron Deficiency - Chen, Lin; Wang, Gaopeng; Chen, Pengfei; Zhu, Honglei; Wang, Shaohua; Ding, Yanfeng (Frontiers in Plant Science, 2018)
Iron (Fe) is an essential mineral element required for plant growth, and when soil availability of Fe is low, plants show symptoms of severe deficiency. Under conditions of Fe deficiency, plants alter several processes to acquire Fe from soil. In this study, we used rice cultivars H 9405 with high Fe accumulation in seeds and Yang 6 with low Fe accumulation in seeds to study their physiological responses to different conditions of Fe availability. In both shoots and roots, the responses of ROS enzymes, leaf and root ultrastructure and photosynthetic system to iron deficiency in Yang 6 were much greater sensitive than those in H 9405. For the distribution of iron, the iron content was much higher in roots of Yang 6, in contrast to higher shoot content in H 9405. Differential responses were shown with the Fe content in roots and shoots, which were the opposite in the two varieties; thus, we proposed the existence of long-distance signals. Then a split root and shoot removal experiments wereas used to demonstrate that a long-distance signal was involved in the iron-deficient rice plant, and that the signal strength was highly correlated with the functional leaves.